Treatment of osteochondral injuries with platelet gel - Danieli, Marcus Vinicius [UNESP]; Pereira, Hamilton da Rosa [UNESP]; Sa Carneiro, Carlos Augusto de [UNESP]; Felisbino, Sergio Luiz [UNESP]; Deffune, Elenice [UNESP] (Hospital Clinicas, Univ Sao Paulo, 2014)
OBJECTIVES: Treatments for injured articular cartilage have not advanced to the point that efficient regeneration is possible. However, there has been an increase in the use of platelet-rich plasma for the treatment of several orthopedic disorders, including chondral injuries. Our hypothesis is that the treatment of chondral injuries with platelet gel results in higher-quality repair tissue after 180 days compared with chondral injuries not treated with gel.METHODS: A controlled experimental laboratory study was performed on 30 male rabbits to evaluate osteochondral injury repair after treatment with or without platelet gel. Osteochondral injuries were surgically induced in both knees of each rabbit at the medial femoral condyle. The left knee injury was filled with the platelet gel, and the right knee was not treated. Microscopic analysis of both knee samples was performed after 180 days using a histological grading scale.RESULTS: The only histological evaluation criterion that was not significantly different between treatments was metachromasia. The group that was treated with platelet gel exhibited superior results in all other criteria (cell morphology, surface regularity, chondral thickness and repair tissue integration) and in the total score.CONCLUSION: The repair tissue was histologically superior after 180 days in the study group treated with platelet gel compared with the group of untreated injuries.
Keywords: Platelet-Rich Plasma; Articular Cartilage; Injuries; Regenerative Medicine